RELIABILITY AND PRODUCTIVITY ANALYSIS OF COLD ROLLING PRODUCTION UNITS: INSIGHTS FROM OBJECTIVE MATRIX AND 5-WHY’S ANALYSIS METHODS - Arifa, Dhinar Elma; Kirana, Nabila Lintang; Ulung, Manik Purbo; Annisa, Putri Dwi (Journal of Industrial Engineering Management, 2024)
The research on increasing productivity using the Objective Matrix (OMAX) and the 5-Whys problem-solving method in a manufacturing company that produces coil steel can be applied in the steel industry with a competitive advantage. The OMAX method is used to measure productivity and determine the appropriate productivity criteria for the existence of a particular department. The 5-Whys problem-solving method is used to detect factors that affect productivity and identify solutions to overcome them. The research can be conducted by collecting data on productivity levels, productivity criteria, and factors that affect productivity. This data can be obtained through systematic measurement and analysis. The results of the research can be used to identify factors that affect productivity, measure productivity levels, and identify solutions to overcome them. The research can be beneficial for a manufacturing company that produces coil steel in developing strategies to increase productivity.